Compaction behavior of continuous carbon fiber tows: an experimental analysis. (4th November 2015) - Kastanis, D.; Steiner, H.; Fauster, E.; Schledjewski, R.
Graphical Abstract: Abstract : The compaction behavior of continuous carbon fiber tows was experimentally studied by means of laser light sectioning method. This method allows a direct measurement of tow cross-sectional dimensions during continuous processes. In this work the carbon fiber tows are axially stressed and laid on a curved structure in order to examine their compaction behavior on a smooth surface. The results show a similar compaction behavior for all studied carbon fiber tows that is independent of the tow size.